Evolutionary comparisons predict that dimerization of human cytochrome P450 aromatase increases its enzymatic activity and efficiency. Issue 154 (November 2015) - Martin, Lisandra L.; Holien, Jessica K.; Mizrachi, Dario; Corbin, C. Jo; Conley, Alan J.; Parker, Michael W.; Rodgers, Raymond J.
Graphical abstract: Highlights: Porcine gonadal P450 aromatase has higher affinity and lower activity than human. Biophysical analysis indicated that human but not porcine P450 aromatase is a dimer. In silico analysis identified the site of homo-dimerization in human. Structure of the porcine gonadal aromatase is unlikely to form dimers. Conclude that dimerization of aromatase affects affinity and activity. Abstract: Estrogen is an essential vertebrate hormone synthesized from androgens involving multiple hydroxylations, catalyzed by cytochrome P450 aromatase (P450arom or CYP19) enzymes. Despite their importance, very few comparative studies have been conducted on vertebrate and/or mammalian P450arom enzymes, either structurally or functionally. Here we directly compared the human ( h -) and porcine gonadal ( pg -) P450arom, as pg -P450arom has very low catalytic efficiency, with a ten-fold higher affinity ( Km ) for a substrate (androstenedione) and ten-fold reduction in turnover ( V max ). We recombinantly expressed these proteins and compared their interactions on a membrane using a quartz crystal microbalance (QCM) and also with the electron donor protein cytochrome P450 oxidoreductase (CPR). Changes in frequency and dissipation in the QCM supported the h -P450arom forming a homodimer that agreed with the FRET data, but not pg -P450arom. Analysis of the X-ray crystal structure of the h -P450arom suggested a likely site of homo-dimerization and found that certain key interacting residues were not conserved in pg -P450arom. Molecular dynamics simulations provide support for the importance of these residues in homo-dimerization. Here we propose that the lower affinity and higher activity with reduced release of intermediate metabolites by the h -P450arom is as a consequence of its ability to form homodimers. The functional implications of dimerization provide an important mechanistic step in the requirement for efficient aromatization.